2010
DOI: 10.1002/bip.21493
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of the biosynthetic gene clusters of coumermycin A1, clorobiocin and caprazamycins in genetically modified Streptomyces coelicolor strains

Abstract: The biosynthetic gene clusters of the aminocoumarin antibiotics clorobiocin and coumermycin A(1) and of the liponucleoside antibiotic caprazamycin were stably integrated into the genomes of different host strains derived from Streptomyces coelicolor A3(2). For the heterologous expression of clorobiocin derivatives in a chemically defined medium, inclusion of 0.6% of the siloxylated ethylene oxide/propylene oxide copolymer Q2-5247 into the growth medium proved to result in a 4.8-fold increase of productivity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…This is particularly important for heterologous expression of biosynthetic gene clusters that are being uncovered at a high rate in actinomycetes in the era of genome sequencing. In particular, the combination of synthetic biology approaches with expression in optimized heterologous Streptomyces production platforms is a promising development (403)(404)(405)(406)(407)(408).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
“…This is particularly important for heterologous expression of biosynthetic gene clusters that are being uncovered at a high rate in actinomycetes in the era of genome sequencing. In particular, the combination of synthetic biology approaches with expression in optimized heterologous Streptomyces production platforms is a promising development (403)(404)(405)(406)(407)(408).…”
Section: Correlation Between Growth and Antibiotic Productionmentioning
confidence: 99%
“…[48] We recently showed that S. coelicolor M1154 represents an excellent host strain for the heterologous production of liponucleoside antibiotics. [49] Therefore, the generated cosmid npsXT01 was introduced into S. coelicolor M1154 by triparental intergeneric conjugation, and three kanamycin resistance clones were selected. Extracts of cultures from the napsamycin producer strain Streptomyces sp.…”
Section: Heterologous Expression Of the Napsamycin Gene Clustermentioning
confidence: 99%
“…This minimized strain was successfully used for heterologous production of different classes of NPs with signi fi cant titers, e.g., aminoglycosides, nonribosomal peptides, polyketides and terpenes (Komatsu et al 2010 ) . Other related researches in S. coelicolor and E. coli further con fi rmed the superiority of genome minimized strains for various valuable compounds production (Flinspach et al 2010 ;Mizoguchi et al 2007 ) . Further improvements will be focused on the construction of biotechnologically synthetic platform cell with a minimized genome and ef fi cient regulatory structure, which can be easily customized for various pre-de fi ned tasks from producing therapeutics to decontaminating waste streams (Foley and Shuler 2010 ) .…”
Section: Pathway Assembly and Host Redesign For Natural Products Hetementioning
confidence: 97%